Representasi Gender dalam Antologi Cerpen Kitab Kawin Karya Laksmi Pamuntjak - Heni Rugun Siregar; Liza Septa Wilyanti; Ulil Amri (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2026)
This study aims to represent female characters in the short story anthology "Kitab Kawin" by Laksmi Pamuntjak. The study uses a qualitative descriptive method with a Roland Barthes semiotic approach. The research data consists of quotations containing representations of injustice towards female characters. Data collection was carried out through reading and note-taking techniques, while data analysis was carried out by identifying signifiers, signifieds, denotations, connotations, and myths. The results of the study indicate that there are five forms of injustice towards female characters: marginalization, subordination, stereotypes, double workload, and violence. Marginalization is seen through restrictions on access to education and opportunities for self-development. Subordination is shown through women's limitations in making life choices. Stereotypes are evident in labeling women as weak, emotional, and bound by certain beauty standards. The double workload is seen when women must simultaneously carry out domestic and public roles. Meanwhile, violence is represented through physical and psychological actions experienced by female characters. The research findings indicate that patriarchal culture remains a major factor in injustice towards women in social and family life.